Evaluating the Pattern of Use and Direct Cost of Injectable Antibiotics Before and After Health Transformation Plan at Namazi Hospital in Shiraz - Shokooh Behdadian; Sakhajoo Nikoo; Fatemeh Soleymani; Afsaneh Vazin; Laleh Mahmoudi; Faezeh Abdizadeh; Iman Karimzadeh (Journal of Pharmacoeconomics and Pharmaceutical Management)
Background: The inappropriate use of antimicrobials in outpatient and inpatient settings has led to the spread of microbial resistance, reduced clinical effectiveness of antimicrobial drugs, and significant direct and indirect costs. Various programs have been implemented to improve antimicrobial usage patterns. The study examined how the Health Transformation Plan (HTP) affected prescribing injectable antibiotics and costs at a referral teaching hospital.